Effect of sodium montmorillonite source on nylon 6/clay nanocomposites - Fornes, T.D.; Hunterb, D.L.; Paul, D.R.
The effect of sodium montmorillonite source on the morphology and properties of nylon 6 nanocomposites was examined using equivalent experimental conditions. Sodium montmorillonite samples acquired from two well-known mines, Yamagata, Japan, and Wyoming, USA, were ion exchanged with the same alkyl ammonium chloride compound. The resulting organoclays were extruded with a high molecular weight grade of nylon 6 under the same processing conditions. Quantitative analysis of TEM photomicrographs of the two anocomposites reveal a slightly larger average particle length and a slightly higher degree of platelet exfoliation for the Yamagata based nanocomposite than the Wyoming version, thus, translating into a higher particle aspect ratio. The stress-strain behavior of the nanocomposites appears to reflect the nanocomposite morphology, in that higher stiffness and strengths are attainable with the increased particle aspect ratio. Moreover, the trends in stiffness behavior between the two types of nanocomposites may be explained by conventional composite theory.
Keywords: NYLON 6; NANOCOMPOSITES; MONTMORILLONITE